Apoplexy of microprolactinomas during pregnancy: report of five cases and review of the literature. Issue 1 (24th May 2021) - Kuhn, Emmanuelle; Weinreich, Alexandra A; Biermasz, Nienke R; Jorgensen, Jens Otto L; Chanson, Philippe
Abstract : Context: Prolactinomas frequently cause amenorrhoea, galactorrhoea and infertility and require dopamine agonist (DA) treatment to normalize prolactin levels and hence, restore ovulation. The vast majority of female patients harbour microprolactinomas in whom DA treatment is usually discontinued at the time of pregnancy diagnosis and surveillance is generally limited as the symptomatic growth is considered very rare. Case descriptions: We report five cases of women harbouring a microprolactinoma in whom symptomatic pituitary apoplexy occurred during pregnancy. Only one necessitated surgery during pregnancy, while the others were treated conservatively by reintroducing DAs in three. A systematic literature review found reports of four additional cases among 20 cases of prolactinomas (both macro- and micro-prolactinomas) complicated by apoplexy during pregnancy. Conclusion: During pregnancy, pituitary apoplexy may occur in pre-existing microprolactinomas, causing tumour enlargement and headache, which may be self-limiting but may require intervention by re-initation of dopamine agonists or surgery. Our literature review confirms that this clinical event is rare; nevertheless, physicians managing pregnant patients with microprolactinomas must be aware that symptomatic pituitary apoplexy may incidentally occur in all trimesters of pregnancy and require prompt radiological, endocrine and ophthalmological assessment and treatment.